Morphophysiological characterization in artichoke accessions aimed at selecting materials for in natura consumption - Costa, Angélica Reolón da (2012)
A morphophysiological characterization of 19 accessions within an artichoke germplasm collection was conducted with the aim of determining genetic variability and to select materials suitable for in natura consumption to be used in genetic breeding. The collection was composed of commercial accessions, materials collected in South Brazil, and of foreign origin. Twenty quantitative, five multicategorical and two binary traits were evaluated. Quantitative data were submitted to a multivariate analysis. Genetic variability was observed for almost all characteristics. The traits with the greatest relative contribution to genetic divergence, which accounted for 79.54% of the variability, were as follows: the thickness and diameter bottom, bottom fresh mass/head fresh mass ratio, external bract length, bracts base, leaves and primary head height and plant diameter, primary head diameter and bracts base thickness. A cluster analysis revealed four groups. Group I aggregated the accessions with characteristics for fresh consumption. The best accessions were Romanesco 1, Green Globe, and Improved Green Globe, all of which exhibited plants with a greater fresh mass, larger primary head diameter, greater fresh mass and bottom diameter, circular head shape, no thorns, round head tip and desired color, that are important traits for selection of superior genotypes for in natura consumption.